Fluorogenic nanoreactor assembly with boosted sensing kinetics for timely imaging of cellular hydrogen peroxide. Issue 6 (9th November 2015) - Heo, Jeongyun; Lim, Chang-Keun; Kim, Youngsun; Cho, Hong-Jun; Lee, Yong-Deok; Maeng, Joon-ho; Ahn, Dae-Ro; Lee, Sangyoup; Bang, Joona; Park, Soo Young; Kim, Sehoon
Abstract : Nanoscopic catalysis: a reactor-like nanoprobe with enzyme-like boosted sensing kinetics is reported. Abstract : The precise detection of endogenous H2 O2 has been considered to be a useful tool for understanding cell physiology. Here, we have developed a nanoreactor co-incorporated with a H2 O2 -responsive fluorogenic molecule and a catalytic additive. The fast sensing kinetics allows us to visualize a subcellular response in real-time.